Evaluating the potentials and challenges of agritourism development in Golestan Province, Iran: a clustering and risk analysis - Seyyed Najib Hosseini; Vali Borimnejad; Hadi Rahmani-Fazli; Sahar Dehyouri (Discover Sustainability)
Abstract This study examines the potential and challenges of developing agritourism in Golestan Province, Iran, focusing on its role in sustainable rural development. Data was collected from 325 farms and agritourism centers through standardized questionnaires and ten semi-structured interviews. Descriptive statistics, correlation analysis, clustering, and risk assessment were used to analyze the data. The clustering results divided the province’s cities into three groups based on high, medium, and low potential for agritourism development. Gorgan was identified as the central hub of agritourism in the province. At the same time, cities such as Aliabad Katul and Gonbad-e Kavus require improved infrastructure and tourism services to realize their full potential. Meanwhile, cities like Maraveh Tappeh and Bandar Torkaman, with lower potential, need special planning and developmental efforts. The risk analysis identified environmental risks, such as climate change, water shortages, and infrastructure challenges, as the main threats to agritourism development in the province. The study suggests that improving infrastructure, raising public awareness, and managing risks are essential to achieving sustainable development in this area. Theoretically, this research contributes to a deeper understanding of the role of agritourism in rural development. At the same time, it offers practical recommendations for policymakers and decision-makers to achieve sustainable agritourism development by enhancing infrastructure and improving visitor experiences.